2017
DOI: 10.1111/jgs.14944
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Associated with Higher Risk of Dementia: Population‐Based Cohort Study in Taiwan

Abstract: Subjects who had more severe PD or did not receive periodontal treatment were at greater risk of developing dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 44 publications
3
85
0
1
Order By: Relevance
“…Our findings are in agreement with recent findings from epidemiological studies reporting a significant association between periodontitis and cognitive impairment, although very few of these studies involved detailed clinical evaluations of periodontal status. One strength of the current study is that we used data from full‐mouth assessments of periodontal status involving examinations of six sites on all teeth, allowing us to define periodontitis by two commonly used case definitions as well as calculate PISA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in agreement with recent findings from epidemiological studies reporting a significant association between periodontitis and cognitive impairment, although very few of these studies involved detailed clinical evaluations of periodontal status. One strength of the current study is that we used data from full‐mouth assessments of periodontal status involving examinations of six sites on all teeth, allowing us to define periodontitis by two commonly used case definitions as well as calculate PISA.…”
Section: Discussionsupporting
confidence: 93%
“…A putative link between periodontitis and cognitive impairment/dementia has been reported . There are several possible underlying mechanisms for this association.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 However, most investigations have reported an association of periodontitis or tooth loss with cognitive function or the presence of dementia, suggesting the involvement of peripheral inflammation as a likely causal factor, although this relationship was not addressed in these studies. 12,[22][23][24] A recent study in a broad Taiwanese sample concluded that periodontitis in the older adult was associated with a greater risk of developing dementia (hazard ratio:1.16), 44 but there was no examination of underlying physiopathological mechanisms.…”
Section: Discussionmentioning
confidence: 99%